WOUND INFECTION AFTER THERAPEUTIC TOOTH EXTRACTION WITH AND WITHOUT ANTIBIOTICS - DR. P. U. ABDUL WAHAB; DR. MADHU LAXMI.M; DR. P. SENTHIL NATHAN (International Journal of Pharma and Bio Sciences, 2013)
An analgesics and antibiotics are generally prescribed following extraction of the teeth. However, the role of antibiotics is controversial in clean contaminated wounds. Most of the oral surgeon’s advice antibiotics for extraction of non-infected teeth and this causes side effects. The purpose of this study was to find out whether antibiotic is necessary for the prevention of infection after therapeutic extraction Settings and Design - This is a prospective pilot clinical trial. 62 patients who required therapeutic extractions for orthodontic treatment were divided randomly into two equal groups. Group I were given an analgesic. Group II were given an antibiotic and an analgesic following the extraction. Infection rates were compared between the two groups on the 3rd and 5th post extraction day. Corrected Chi-Square test was performed. No significant difference was found between the two groups withreference to the incidence of infection. Thence,we conclude that antibiotics are not essential for therapeutic extractions.